2020
DOI: 10.3390/vaccines8020299
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Modified Chitosan-Nanoparticle-Based Salmonella Subunit OralVaccine-Induced Immune Response and Efficacy in a Challenge Trial in Broilers

Abstract: Controlling Salmonella enterica serovar Enteritidis (SE) infection in broilers is a huge challenge. In this study, our objective was to improve the efficacy of a chitosan nanoparticle (CS)-based Salmonella subunit vaccine for SE, containing immunogenic outer membrane proteins (OMP) and flagellin (FLA), called the CS(OMP+FLA) vaccine, by surface conjugating it with mannose to target dendritic cells, and comparing the immune responses and efficacy with a commercial live Salmonella vaccine in broilers. The CS(OMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
4
17
0
Order By: Relevance
“…However, there are currently no killed vaccines that are delivered through the oral route to provide dual systemic and mucosal protection for poultry flocks. Recent research has adapted the use of modern nanotechnology to improve the poultry industry [ 78 , 80 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. The use of a biodegradable nanoparticle that protects the vaccines antigens from the harsh pH of the GIT and that can be “programmed” to deliver the antigens to the intestinal PPs is a new step towards innovative vaccines.…”
Section: A Novel Approach To Poultry Vaccination: Nanoparticles Vaccines Against Salmonella For Use In Broilers and Lamentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are currently no killed vaccines that are delivered through the oral route to provide dual systemic and mucosal protection for poultry flocks. Recent research has adapted the use of modern nanotechnology to improve the poultry industry [ 78 , 80 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. The use of a biodegradable nanoparticle that protects the vaccines antigens from the harsh pH of the GIT and that can be “programmed” to deliver the antigens to the intestinal PPs is a new step towards innovative vaccines.…”
Section: A Novel Approach To Poultry Vaccination: Nanoparticles Vaccines Against Salmonella For Use In Broilers and Lamentioning
confidence: 99%
“…Few studies have assessed the effects of Salmonella chitosan nanoparticle vaccines in chickens. Recent studies designed and demonstrated the immune response of broilers and layers to an oral chitosan nanoparticle (CNP)-based vaccine against Salmonella [ 78 , 102 , 103 , 104 , 105 , 106 , 107 ]. For these studies, the Salmonella subunit CNP vaccine was synthesized to contain S. enteritidis immunogenic outer membrane proteins (OMPs) and flagellin protein combined with a flagellin surface coating.…”
Section: A Novel Approach To Poultry Vaccination: Nanoparticles Vaccines Against Salmonella For Use In Broilers and Lamentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, lower dose (10 µg antigen), vaccination at young age (3rd day), and two or three doses of nanovaccine administration heightened the systemic and mucosal antibody, cell mediated immune response, TLRs gene expression, resulting in reduced S. Enteritidis load in the cecum (Han et al, 2020a). Mannose receptor is expressed on dendritic cells and macrophages, targeting them using mannose ligand conjugated nanovaccine elicited enhanced cell mediated immune response, and in without mannose conjugated nanovaccine received birds observed increased mucosal antibody response, while both the nanovaccines formualtions reduced the challenge Salmonella load in the intestines comparable to a commercial live vaccine (Han et al, 2020b). Altogether, our broiler experiments revealed that the selection of antigen, vaccine dose, age of birds vaccinated and the type of modifications on CS NPs are important to achieve robust immune response and protective efficacy against Salmonella.…”
Section: Cs Nps Based Vaccines For Bacterial Infectious Diseasementioning
confidence: 99%
“…Negatively charged nanovaccines with a size smaller than 100 nm may have potentially more specific immunomodulatory capacity, as they do not interact with positively charged non-immune cells [45]. The capacity for antigen-associated NPs to elicit immune responses can be strengthened by incorporating targeting moieties on the NP surface to improve their recognition by APCs [46][47][48][49][50]. Various targeting moieties, such as mannose and antibodies, have been used for this purpose for different subsets of APCs [48,49,51,52].…”
Section: Introductionmentioning
confidence: 99%